Empowering the Mina Asri Catfish Farming Group Through Digital Marketing and Financial Literacy for Business Sustainability - Ida Ayu Putu Santi PURNAMAWATI; A.A Ngr Gde Punia Artawan PUTRA; I Ketut Johny Pramanda PUTRA (PT Keberlanjutan Strategis Indonesia, 2025)
Indonesia, as a maritime nation, has significant potential in the fisheries sector, with catfish being one of the main freshwater aquaculture commodities. In Bali, the Mina Asri Catfish Farming Group contributes to local fishery production, yet faces challenges in production costs, limited marketing strategies, and manual financial management. This study aims to empower the group through innovation and community service activities that enhance production efficiency, market competitiveness, and financial literacy. The program was implemented through stages of socialization, training, technology application, and mentoring. Training focused on the use of alternative pellet feed, digital marketing through social media, and digital financial recording using simple applications. Results showed that providing pellet feed assistance reduced production costs by at least 10% per cultivation cycle, thereby improving profit margins and financial allocation for other development needs. Digital marketing training increased members’ skills in content creation and online promotion, enabling expansion of product distribution, particularly for processed catfish, beyond local markets. Meanwhile, financial literacy training facilitated the adoption of digital records, improving transparency and supporting more accurate evaluation of profitability. Pre- and post-test assessments demonstrated a 70% improvement in participants’ knowledge and skills, confirming the effectiveness of the program. In conclusion, the empowerment program significantly improved group capacity in production, marketing, and financial management. Active community participation played a crucial role in ensuring sustainability, with the program contributing to business independence, enhanced income, and regional food security, while also strengthening the community-based economy.